Receipt of the C-terminal Tail from a Neighboring λ Int Protomer Allosterically Stimulates Holliday Junction Resolution - Hazelbaker, Dane (2005)
Bacteriophage λ integrase (Int) catalyzes the integration and excision of the phage λ chromosome into and out of the Esherichia coli host chromosome. The seven carboxy-terminal residues (C-terminal tail) of Int comprise a context-sensitive regulatory element that links catalytic function with protein multimerization and also coordinates Int functions within the multimeric recombinogenic complex. The experiments reported here show that the β5-strand of Int is not simply a placeholder for the C-terminal tail but rather exerts its own allosteric effects on Int function in response to the incoming tail. Using a mutant integrase in which the C-terminal tail has been deleted (W350ter), we demonstrate that the C-terminal tail is required for efficient and accurate resolution of Holliday junctions by tetrameric Int. Addition of a free heptameric peptide of the same sequence as the C-terminal tail partially reverses the W350ter defects by stimulating Holliday junction resolution. The peptide also stimulates the topoisomerase function of monomeric W350ter. Single residue alterations in the peptide sequence and a mutant of the β5 strand indicate that the observed stimulation arises from specific contacts with the β5 strand (residues 239–243). The peptide does not stimulate binding of W350ter to its cognate DNA sites and therefore appears to recapitulate the effects of the normal C-terminal tail intermolecular contacts in wild-type Int. Models for the allosteric stimulation of Int activity by β5 strand contacts are discussed.